Pengaruh Inflasi dan BI Rate Terhadap Pembiayaan Usaha Mikro Kecil dan Menengah (Studi Kasus Pada Bank Umum Syariah) - JAYANTI, SRI DELASMI; DEKY, DEKY ANWAR (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
This study aimed to analyze the effects of inflation and BI rate on UKMK financing in (BUS) from period 2010-2015. The research sample was taken from six banks. The method of sampling was done by using purposive sampling, which is sampling technique with a certain considerations. The hypothesis testing methods used were multiple linear regression analysis. Partial results of this study indicated that inflation has a significant effect on UKMK financing, while the BI Rate no significant effect on the financing of UKMK. Simultaneously, inflation and BI rate influenced UKMK financing.Kata kunci: Inflasi, Bi Rate, Pembiyaan UMKM